Differences in the Rate of in Situ Mammary Gland Development and Other Developmental Endpoints in Three Strains of Female Rat Commonly Used in Mammary Carcinogenesis Studies: Implications for Timing of Carcinogen Exposure. (October 2016) - Stanko, Jason P.; Kissling, Grace E.; Chappell, Vesna A.; Fenton, Suzanne E.
The potential of chemicals to alter susceptibility to mammary tumor formation is often assessed using a carcinogen-induced study design in various rat strains. The rate of mammary gland (MG) development must be considered so that the timing of carcinogen administration is impactful. In this study, in situ MG development was assessed in females of the Harlan Sprague-Dawley (Hsd:SD), Charles River Sprague-Dawley (Crl:SD), and Charles River Long-Evans (Crl:LE) rat strains at postnatal days 25, 33, and 45. Development was evaluated by physical assessment of growth parameters, developmental scoring, and quantitative morphometric analysis. Although body weight (BW) was consistently lower and day of vaginal opening (VO) occurred latest in female Hsd:SD rats, they exhibited accelerated pre- and peripubertal MG development compared to other strains. Glands of Crl:SD and Crl:LE rats exhibited significantly more terminal end buds (TEBs) and TEB/mm than Hsd:SD rats around the time of VO. These data suggest a considerable difference in the rate of MG development across commonly used strains, which is independent of BW and timing of VO. In mammary tumor induction studies employing these strains, administration of the carcinogen should be timed appropriately, based on strain, to specifically target the peak of TEB occurrence.